Waste glass as partial mineral precursor in alkali-activated slag/fly ash system. (December 2017) - Zhang, Shizhe; Keulen, Arno; Arbi, Kamel; Ye, Guang
Abstract: The feasibility of a waste glass powder residue (GP) from glass recycling as partial mineral precursor to produce alkali-activated materials is investigated. GP served as powder coal fly ash (PCFA) replacement within a reference system composed of 50% PCFA and 50% ground granulated blast furnace slag (GGBS). Compared with PCFA, GP was better involved in the alkali activation process by having a higher silica and Ca dissolution. Furthermore, increasing GP replacement up to 30% prolonged the induction period, facilitated the gel formation and yielded a 35% higher 28-day compressive strength. These observations are similar to the effect of using both sodium hydroxide and sodium silicate as alkali activator in alkali-activated slag/fly ash systems. A higher polymerization of the gel network was also observed. Microstructure analysis indicated that the main reaction product is a calcium silicate hydrate type gel substituted with Al and Na (C-(N)-A-S-H type gel). This work largely contributes to the understanding of the reactivity and potential of GP and promotes its practical utilization as a mineral precursor in the production of alkaline cements.